Criminal Liability in Premeditated Murder Cases Through the Michat Application - Shadrach Christo Funakosi Simorangkir; Sriono Sriono; Wahyu Simon Tampubolon (International Journal of Science and Environment (IJSE), 2026)
The development of information technology has had a significant impact on various aspects of life, including the modus operandi of criminal acts. This article discusses criminal liability in a case of premeditated murder mediated by the MICHAT friendship application. The case study focuses on the Bengkalis District Court Decision Number 186/Pid.B/2025/PN Bis, which sentenced defendant Arif Indra Lexmana Shiombing to 13 years in prison. This research uses a normative juridical method with a case study approach. The results show that the elements of intent and planning (dolus et premeditatio) in Article 340 of the Criminal Code are legally and convincingly proven, even though the initial motive was not to kill, but rather as a form of revenge for the fraud experienced by the defendant. These findings underscore the importance of adaptive law enforcement to technological developments, as well as the need for sociological and psychological considerations in sentencing.